2017
DOI: 10.1111/bph.14046
|View full text |Cite
|
Sign up to set email alerts
|

BK β1 subunit‐dependent facilitation of ethanol inhibition of BK current and cerebral artery constriction is mediated by the β1 transmembrane domain 2

Abstract: BK β1 TM2 is necessary for this subunit to enable ethanol-induced inhibition of myocyte BK channels and cerebral artery constriction at physiological Ca and voltages. Thus, novel agents that target β1 TM2 may be considered to counteract ethanol-induced cerebral artery constriction and associated cerebrovascular conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
(148 reference statements)
0
5
0
Order By: Relevance
“…Therefore, vascular SM BK channel activators are effective vasodilators, as reviewed in [93] while genetic ablation of the BK β1 subunit (e.g., in the KCNMB −/− mouse) is associated with increased myogenic tone [18]. Finally, β1 subunits embolden BK channels with distinct pharmacology, including channel activation by 17β-estradiol [180], micromolar levels of hydrophobic cholanes and their nonsteroidal analogs [22,23,29,132], leukotriene B4 [24], dehydrosoyasaponin-I [131], hydroclorothiazide [127], equol [203], tungstate [57], increased sensitivity to PIP 2 [179] and DHA [74,75], and ethanol-induced reduction of channel activity at low μM Ca 2+ ic [94,95]. The role of SM BK channels as pharmaco-therapeutic targets has been recently reviewed elsewhere [93,219].…”
Section: Basic Phenotype Of the Vascular Smooth Muscle Bk Channel Andmentioning
confidence: 99%
“…Therefore, vascular SM BK channel activators are effective vasodilators, as reviewed in [93] while genetic ablation of the BK β1 subunit (e.g., in the KCNMB −/− mouse) is associated with increased myogenic tone [18]. Finally, β1 subunits embolden BK channels with distinct pharmacology, including channel activation by 17β-estradiol [180], micromolar levels of hydrophobic cholanes and their nonsteroidal analogs [22,23,29,132], leukotriene B4 [24], dehydrosoyasaponin-I [131], hydroclorothiazide [127], equol [203], tungstate [57], increased sensitivity to PIP 2 [179] and DHA [74,75], and ethanol-induced reduction of channel activity at low μM Ca 2+ ic [94,95]. The role of SM BK channels as pharmaco-therapeutic targets has been recently reviewed elsewhere [93,219].…”
Section: Basic Phenotype Of the Vascular Smooth Muscle Bk Channel Andmentioning
confidence: 99%
“…We have previously documented the finding that EtOH inhibition of BK channels at physiological levels of Ca 2+ found in cerebrovascular myocytes requires the presence of modulatory, smooth muscle-abundant BK β1 subunits [ 25 ]. Moreover, the β1 subunit TM2 acts as a specific EtOH sensor [ 35 ]. In contrast, PREG-induced inhibition of these channels does not involve β1 regulatory proteins; instead, channel-forming α subunits suffice for steroid action [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, it has previously been shown by our group that smooth muscle BK channel inhibition and eventual MCA constriction are dependent on the presence of BK regulatory subunits of β1 type, which are abundant in cerebrovascular smooth muscle [ 25 , 32 ]. In particular, the TM2 domain of this accessory subunit serves as an alcohol sensor [ 35 ]. In contrast, PREG inhibits MCA smooth muscle BK channels and thus evokes constriction via its recognition by the channel-forming subunit [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a rat model widely used to mimic human cerebral artery function, we previously demonstrated that cerebrovascular constriction evoked by 10–100 mM ethanol in vivo and in vitro involves drug-induced reduction of ionic current mediated by voltage-/calcium-gated, large conductance K + (BK) channels in the vascular smooth muscle (SM) (Liu et al, 2004; Bukiya et al, 2014). This inhibition may result from direct sensing of ethanol by the BK proteins (Bukiya et al, 2009; Kuntamallappanavar & Dopico, 2017) and/or BK channel modulation by ethanol-sensitive parties other than BK itself, e.g., ryanodine receptors (Ye et al, 2014).…”
Section: Introductionmentioning
confidence: 99%